2021
DOI: 10.1111/nph.17374
|View full text |Cite
|
Sign up to set email alerts
|

Primary tissues may affect estimates of cavitation resistance in ferns

Abstract: Different methods of measuring cavitation resistance in fern petioles lead to variable results, particularly with respect to the P 50 metric. We hypothesised that the fern dictyostele structure affects air entry into the xylem, and therefore impacts the shape of the vulnerability curve.Our study examined this variation by comparing vulnerability curves constructed on petioles collected from evergreen and deciduous ferns in the field, with curves generated using the standard centrifuge, air-injection and bench-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…To our knowledge, no study has documented the relationship between stelar architecture and vulnerability to drought‐induced embolism in the stems of any vascular plant lineage. However, work on this level of vascular construction in fern leaves indicates that increased dissection confers increased drought resistance (Brodersen et al ., 2012; Pitterman et al ., 2021). It has also been shown that the leaves of certain fern species with dissected vascular architectures are highly drought resistant (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, no study has documented the relationship between stelar architecture and vulnerability to drought‐induced embolism in the stems of any vascular plant lineage. However, work on this level of vascular construction in fern leaves indicates that increased dissection confers increased drought resistance (Brodersen et al ., 2012; Pitterman et al ., 2021). It has also been shown that the leaves of certain fern species with dissected vascular architectures are highly drought resistant (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, it has been demonstrated that larger conduits and thinner pit membranes are both correlated with higher vulnerability to drought-induced embolism in the petiole (Pittermann et al, 2011;Brodersen et al, 2014). At the architectural level, two studies have suggested that increased architectural dissection (greater separation of the vasculature into discrete 'bundles') in the leaf may increase drought resistance (Brodersen et al, 2012;Pitterman et al, 2021), an analogous trend to increasing embolism resistance with increased vessel dissection in woody plants (Loepfe et al, 2007). At the histological level, nothing is known about the effects of xylem tissue organization on embolism resistance in ferns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fern rhizomes function as holdfasts and can be difficult to work with because they are often mucilaginous and contorted. Hence, our efforts focused on the petioles, as in earlier studies, because the petioles support the pinnae, an arrangement analogous to twigs supporting leaves (Watkins et al ., 2010; Holmlund et al ., 2016; Pittermann et al ., 2021). Of the 39 species sampled, hydraulic measures were performed on a subset of 14 species (five epiphytic, three hemiepiphytic, and six terrestrial species), bfecause stipes of the remaining taxa released mucilage upon cutting, and/or copious starch granules, both of which were associated with unusually low flow rates of water when connected to the hydraulic apparatus.…”
Section: Methodsmentioning
confidence: 99%